Investment Attractiveness of the Economy of the World Countries in the Polystructural Space of Foreign Direct Investments - TRUSOVA, Natalia V.; CHERNIAVSKA, Tetiana A.; KYRYLOV, Yurii Y.; HRANOVSKA, Viktoriia H.; SKRYPNYK, Svitlana V.; BOROVIK, Liubov V. (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
The article deals with the theoretical, methodological and practical aspects of ensuring a safety level the investment attractiveness of the world countries economy in the polystructural space of foreign direct investments. In the context of the implementation of investment policy and factors in the field of international investment, an optimization model of the investment attractiveness of the national economy has been developed. The aggregate factors of the investment attractiveness index, which characterize the investment climate, investment activity and the state of economic development of the country, are highlighted. A methodical approach is presented to determine the synergistic impact of foreign direct investment on the country's investment attractiveness indicator. The criteria of normalization of investment attractiveness of the economy of the country by indicators of macroeconomic, monetary and currency status, which are formalized by indicators-stimulators, destimulators and interaction of bilateral boundary constraints are proposed. The criteria of identification of risks and threats of safe and dangerous state of development of the economy of the countries by the methods of prognostic extrapolation of foreign direct investment are taken into account. A comparative assessment of global foreign direct investment flows and global GDP, the value of net sales of cross-border mergers and acquisitions was made. The structure of foreign direct investment by regions of the countries of the world is considered, taking into account their external reserves of investment potential. The indicators of investment attractiveness of the Ukrainian economy and its cooperation with EU countries in terms of the volume of inflow and direct investments are presented. The scenarios for the growth of foreign direct investments in the polystructural space of the world and developing countries are proposed.